2019
DOI: 10.12659/ajcr.915377
|View full text |Cite
|
Sign up to set email alerts
|

A Case of Locally Advanced Breast Cancer in a 59-Year-Old Man Requiring a Modified Approach to Management

Abstract: Patient: Male, 59 Final Diagnosis: Invasive ductal carcinoma Symptoms: Foul-smelling discharge • painful breast mass Medication: — Clinical Procedure: Modified radical mastectomy Specialty: Surgery Objective: Rare disease Background: Male breast cancer is rare, accounting for approximately 1% of all malignancies in men. The lack of awareness of this rare cancer results in delay… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 41 publications
(39 reference statements)
0
5
0
Order By: Relevance
“…Patients are mostly troubled by negative moods [ 19 ]. The humanistic care-centered case management provides patients with good management of postoperative recovery [ 20 ], which facilitates the patients' psychological recovery and elimination of negative emotions [ 21 ]. Our findings indicated that the observation group was superior to the control group in terms of posttraumatic growth ( P < 0.05), which may be attributed to the close monitoring of abnormal conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Patients are mostly troubled by negative moods [ 19 ]. The humanistic care-centered case management provides patients with good management of postoperative recovery [ 20 ], which facilitates the patients' psychological recovery and elimination of negative emotions [ 21 ]. Our findings indicated that the observation group was superior to the control group in terms of posttraumatic growth ( P < 0.05), which may be attributed to the close monitoring of abnormal conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Currently, around 70% to 75% of breast cancer is reported to highly express estrogen receptor alpha (ERα), and the most ERα-positive breast cancer depends on estrogen signaling, which makes these cancers respond well initially to endocrine therapies [ 1 3 ]. Tamoxifen, an estrogen antagonist, is the most successful endocrine therapy for ERα-positive breast cancer [ 4 , 5 ]. Unfortunately, although remarkable benefits of tamoxifen in these treatment settings have been reported, many cases eventually acquired resistance to tamoxifen, thus resulting in relapse and death [ 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…It is presumably due to the fact that the one-to-one case management boosts the patient's selfconfidence in disease management, thereby promoting the recovery of the patient's body function, improving the patient's self-efficacy and self-management behavior, and thus lowering the incidence of postoperative adverse reactions in cancer patients [16]. As previously noted, surgical trauma, disease recurrence, anxiety, and uncertainty of prognosis adversely affect the patients physiologically and psychologically, thereby compromising the patient's treatment compliance [17]. Here, the results revealed that the whole case management mode resulted in higher compliance versus the routine nursing intervention.…”
Section: Discussionmentioning
confidence: 94%